Aggregation and Characterization of ZnO Nano Particles Using Laser Ablation Technique in Ethanol - Aziz, Wisam J; Abid, M A; Mutlk, Hanan Kh (Al-Nahrain Journal of Science, 2017)
In this work, ZnO nanoparticles were snthyesis using pulse laser ablation of zinc target (purity of 99.99%) immersed in ethanol with wave length of Nd:YAG laser (532 nm) operating at different laser energies (700, 800, 900 mJ) with 1Hz and (2000) pulse. A matching of the observed and standard (hkl) planes confirmed that the product is ZnO having a polycrystalline in nature with hexgonal structure perferention in (101) direction.FESEM images showed that NPs have different morphologies and not uniform consist of many small irregular nanoparticles. The surface structure, in the energy 700 mJ has been more uniform compared with others energy.